The comparison of serum concentrations of some elements in healthy and pica affected camels - Gholamali Kojouri; Reza Gharehdaghli; Abdonaser Mohebi (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2021)
Pica is the ingestion of nonfood materials which may occur due to digestive system disorders, metabolic diseases, parasitic infestation and/or some deficiencies and then leads to intoxication, TRP, peritonitis, reticulo-omasal orifice dysfunction, abomasal impaction, abomasitis and intestinal obstruction. In the present study sex, age range and location of camels (Camelus dromedarius) were determined and blood samples were taken before the slaughter. In postmortem examination, forestomach contents of 300 slaughtered camels were carefully examined for the presence of foreign bodies. Blood samples of 20 healthy and 20 camels with pica were used to determine the serum concentrations of iron, copper, zinc, phosphorus, selenium, cobalt and copper to zinc ratio. The results showed that 36 of 300 camels were suffering from pica and the incidence was estimated at 12 percent. Among these, metallic objects with a relative frequency of 33.33% had the highest and woody material with 5.26% had the lowest occurrence. Serum levels of iron, copper, phosphorus, selenium, cobalt and the ratio of copper to zinc in camels with pica were significantly lower than healthy ones. Statistical analysis showed that the serum levels of zinc, copper and phosphorus in male camels with pica were significantly lower and serum levels of cobalt were higher than their female counterparts (p<0.05). It is concluded that deficiencies of iron, copper, phosphorus, selenium and cobalt may play a role in camel pica.